2021
DOI: 10.3390/ijerph18157791
|View full text |Cite
|
Sign up to set email alerts
|

Reopening of Schools in the COVID-19 Pandemic: The Quality of Life of Teachers While Coping with This New Challenge in the North of Spain

Abstract: Background: This study aims to analyze how teachers perceived their quality of life when coping with the reopening of schools after their closure due to the COVID-19 pandemic. Methods: This study was carried out with a total sample of 1633 teachers from the Department of Education of the Basque Autonomous Community (Northern Spain), all of the professionals working in different educational centers, from preschool education to university studies, with the average age of 42.02 years (SD = 10.40). Main Outcome Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Finally, the relationship between perceived organizational support and its implications for commitment has been verified in previous works [ 54 , 55 ]. In the present study, the scores on this variable were shown to reach moderate levels, in line with the results of other studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Interestingly, perceived organizational support was lower in public school teachers, who also perceived more anxiety linked to technostress when teaching during confinement and greater negative family–work interactions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, the relationship between perceived organizational support and its implications for commitment has been verified in previous works [ 54 , 55 ]. In the present study, the scores on this variable were shown to reach moderate levels, in line with the results of other studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Interestingly, perceived organizational support was lower in public school teachers, who also perceived more anxiety linked to technostress when teaching during confinement and greater negative family–work interactions.…”
Section: Discussionsupporting
confidence: 93%
“…Technostress is currently considered a complex syndrome that poses an emerging risk [ 27 ]. In addition, while the research currently available on this topic is still limited [ 28 , 29 ], some studies warn that teachers, particularly at primary and infant levels, are suffering from high levels of general stress that affect their quality of life [ 30 , 31 ], a situation that might favor the development of specific stress resulting from the use of technologies—or, in other words, technostress.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are studies that have analyzed how the fear of COVID can affect the health status of the population, and specifically how it can affect the return to face-to-face teaching activities of teachers and, especially of those with chronic pathology [ 13 , 14 ]. Nevertheless, there are not many studies yet that analyze the aspects related to the return to the classroom of university students.…”
Section: Introductionmentioning
confidence: 99%
“…Although NCAAA and ABET program assessments had considerable differences, ABET data was based on selective courses whereas NCAAA approach was more exhaustive covering all courses, but still the results in Figure 2 do not highlight many variations, as the variation threshold is almost the same for all student outcomes. We also highlight that a sustainable assessment approach requires faculty motivation and support to manage the workload of data collection and analysis [ 31 , 32 ]. Especially in the scenarios where such multiple accreditations are targeted there is a need for dedicated staff to manage the entire process with extensive collaboration with faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a sustainable assessment mechanism requires that the assessment approach is understandable to all stakeholders. In the case of multiple accreditation requirements, it is important to have a unified program mapping to avoid confusion and assessment methods should be overlapped wherever possible to minimize effort and stress on academic staff [ 31 , 32 ]. As Hossain et al [ 5 ] highlighted that institutional and program assessment activities can be merged so our findings highlight that even program accreditation efforts can be combined by developing a unified program mapping and assessment strategy resulting in one continuous improvement action plan.…”
Section: Discussionmentioning
confidence: 99%